ANALYSIS ON THE GRANTING OF DIRECT PAYMENTS IN ROMANIA AND BULGARIA - Eduard Alexandru DUMITRU; Valentina Constanța TUDOR; Marius Mihai MICU; Ana Ruxandra MICU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Both Romania and Bulgaria, the 2014-2020 period is probably a defining period in the country's development, particularly agriculture, taking into account the Commission's intention to abandon the granting of payments in agriculture, after 2020. So, time is critical and highly sensitive, being the last chance to reduce major differences compared to other countries, them benefited from such support on a much higher period than countries new entrants disfavored them up to a large extent thereon. It also represents a tremendous help of direct payments to farmers, contributing to their living standards and continuing their activities in agriculture. This paper seeks to highlight the need for support in agriculture so that by processing the statistical data it can be concluded that in both countries, even after the passing of seven years, regarding the first programming period, the situations are not solved completely, so these measures should be further enforced to help farmers